Residents as Educators: Giving Feedback - Matthew Tews; Kathleen Quinn-Leering; Chris Fox; Jill Simonson; Elizabeth Ellinas; Paul Lemen (Association of American Medical Colleges, 2014)
Abstract This resource is designed to help develop residents and fellows as teachers of medical students. The content addresses an aspect of teaching that many house staff find challenging, that of providing effective formative feedback to medical students on clinical rotations. The materials provided can help improve house staff feedback and meet Liaison Committee on Medical Education and Accreditation Council for Graduate Medical Education expectations regarding interpersonal and communication skills education. There are two interactive presentations with associated video vignettes for instructor use in large or small-groups, as well as instructor guides. Giving feedback can be a challenging aspect of education. This may be particularly difficult for residents and fellows who are not taught how to give quality feedback to medical students. This can lead to a gap in the education of students, as residents and fellows often have the most interaction with students. Both the Liaison Committee on Medical Education and Accreditation Council for Graduate Medical Education recognize the critical role that residents and fellows play in educating medical students and require institutions to provide instruction to house staff on effective teaching. Graduate medical education programs must assume the responsibility for providing residents and fellows with the tools needed to improve their feedback skills, but this is often not the case due to the limited time of faculty members to prepare an engaging and effective presentation on this important educational topic. We developed these two interactive presentations to allow educators to have an already prepared resource that allows them to educate their residents and fellows to give feedback. These presentations touch on the key points of giving feedback and include video vignettes to be included in the presentations. We created these presentations to help our over 80 graduate medical education programs improve their resident/fellow feedback to medical students. Given the range of programs on our campus, the presentations were designed to be appropriate for use by any specialty or subspecialty. We have distributed the presentations to all programs on campus and have made revisions based on feedback.